2011
DOI: 10.1007/s00405-010-1465-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical model for postoperative apnea–hypopnea index after multilevel surgery for sleep-disordered breathing

Abstract: The objective of the study was to formulate a statistical model for postoperative apnea-hypopnea index (AHI) 3 and 12 months after multilevel surgery using the predictors preoperative AHI, body mass index (BMI) and age. The study design was a prospective cohort study. Data of 144 patients were collected prospectively 3 and 12 months after multilevel surgery for obstructive sleep apnea syndrome (OSAS) or upper airway resistance syndrome with excessive daytime sleepiness. The primary endpoint postoperative AHI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…Group A of our patient population was significantly younger than the other groups. However, data from the literature show that age does not affect the outcome of surgery for OSA [2,5,11]. Patients in group B had significantly less nasal surgery than the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A of our patient population was significantly younger than the other groups. However, data from the literature show that age does not affect the outcome of surgery for OSA [2,5,11]. Patients in group B had significantly less nasal surgery than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tonsillectomy has been found to be a decisive factor [4,5]. Patients with accompanying tonsillectomy had a 6-fold higher chance of being a responder in multilevel surgery than patients who had already received tonsillectomy in previous surgery [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Tschopp et al performed a statistical model for multilevel surgery and found that 58% of patients who had a tonsillectomy as part of the multilevel surgery were responders, whereas only 19% of patients who had no tonsillectomy as part of the multilevel surgery were responders . Given the findings in previous studies, tonsillectomy alone could potentially play an important role in improving adult OSA.…”
Section: Introductionmentioning
confidence: 99%
“…4 Multilevel surgery provides a valuable alternative to CPAP therapy especially if conducted in combination with tonsillectomy. When comparing studies on multilevel surgery, special attention should be paid to the rate of tonsillectomy in the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, majority of the patients abandon CPAP therapy because of refusal or intolerance. 4 Though the OSA patients are classically treated with lifestyle modifications and medical management, compliance is poor in these patients and thus warranting surgical management. Surgical modification of airway has been performed since decades but with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%